High humidity electrospinning of porous fibers for tuning the release of drug delivery systems. Issue 12 (13th August 2021) - Ramos, Celia; Lanno, Georg-Marten; Laidmäe, Ivo; Meos, Andres; Härmas, Riinu; Kogermann, Karin
Abstract: Surface porosity of individual electrospun polymeric fibers provides interesting means for controlling fiber behavior for different biomedical applications. In this study porous polycaprolactone (PCL) microfibers were obtained by electrospinning of PCL solution in tetrahydrofuran/dimethyl sulfoxide (DMSO) and chloroform/DMSO at high relative humidity (65%). No pores were formed at low relative humidity (19%). Fibers with different surface porosity and fiber diameter revealed different drug release behavior favoring the release from porous microfibers compared to non-porous and nanofibers compared to microfibers. The results suggest that changing humidity during electrospinning without changing drug-polymer-solvent system enables to tune fiber structure and its release behavior. Graphical Abstract: UF0001